Laryngeal lipoma: A rare cause of pediatric airway obstruction - K.K. Jakobsen; C. Grønhøj; C. Juel; B. Charabi; T. Hjuler (Elsevier, 2018)
Laryngeal lipoma is a rare cause of upper airway obstruction in the pediatric population. We present a case of a 6-year-old boy with a laryngeal lipoma. Diagnosis was subject to doctors-delay, but open neck surgical resection was successful.